Old middle cerebral infarction in a neonate - Hatzidaki, Eleftheria (Radiology and oncology (Ljubljana), 2000)
Background. Cerebral arterial thrombosis is a relatively rare occurrence in the neonatal period. Some children having this condition as neonates, present recurrent local seizures with radiological evidence of acute infarction. Several studies have shown this to be a rare cause of neonatal seizures. Case report. We describe the case of a newborn infant with localized clonic seizures of the lower right extremity on the fourth day of life. Ultrasound examination of the brain showed only mild abnormalities. However Magnetic Resonance Imaging showed evidence of a middle left cerebral arterial infarction. Conclusions. The newer imaging methods, such as central nervous system Magnetic Resonance Imaging can be helpful in the diagnosis of rarer disturbances and can further reveal cases which would otherwise pass unnoticedeven where ultrasound imaging is negative.
Keywords: Cerebral embolism and thrombosis; Cerebral infarction; Diagnosis; diagnostika; Infant, newborn; Infant, newborn, diseases; Magnetic resonance imaging; možganska kap; novorojenčki; Ultrasonography